Phenotypic variability of Calycophyllum spruceanum (Benth.) Hook. f. ex K. Schum. in the peruvian amazonia - Flores Castillo, Gorky (2026)
Calycophyllum spruceanum, commonly known as "capirona", is a tree native to the Peruvian Amazonia, with ecological, cultural and economic importance due to its diverse uses. However, gaps remain in understanding of the morphological traits that significantly contribute to its genetic diversity. This study evaluated 18 C. spruceanum individuals in situ using 34 qualitative and quantitative morphological descriptors (leaf, flower, fruit and seed) and 6 forest descriptors in two forest types in the Tambopata province, Madre de Dios. The results confirmed high variability in forest characteristics (CV > 35% for height and DBH), regardless of forest type (p > 0.05). Multiple correspondence analysis revealed a close association between leaf and flower descriptors (41.9% variability). Simultaneously, principal component analysis explained 44.6% of the total variance using two axes associated with leaf and reproductive morphology, allowing the grouping of individuals into three distinct morphological groups: one with a vegetative emphasis and two with favorable reproductive potential. Strong correlations (r ≥ 0.7) between leaf and reproductive traits support this classification. These findings validate the use of these descriptors as a baseline for identifying promising phenotypes and constitute an essential contribution to establishing ex situ germplasm banks aimed at the conservation and genetic improvement of the species in the Peruvian Amazonia.